Enterprise for the Americas initiative, a partnership for economic liberalization and growth - Whitney, Peter D. ([s.n.] [S.l.], 1991)
Identifies policies that can be implemented to attract the vast amount of capital back into the Latin American and Caribbean region. These are proposed from perspectives of trade, investment, debt and the environment.